861. Health Disparities in HIV and Pregnancy. (26th November 2018) - Abbas, Anum; Aurit, Sarah; Destache, Chris; Horne, John; Gorby, Gary; Vivekanandan, Renuga
Abstract: Background: HIV infection in pregnant females confers a higher risk of morbidity and obstetric complications. Widespread use of anti-retroviral therapy (ART) has dramatically decreased vertical HIV transmission. US HIV-infected pregnant females continue to be at higher risk for obstetric complications compared with nonHIV infected females. This study will be conducted with the objective to estimate the current US morbidity and mortality in HIV-infected pregnant females as well as incidence of obstetric complications in this patient population. Methods: The National Inpatient Sample (NIS) was utilized to identify hospitalizations associated with pregnancy from 2002 to 2014. The aggregation of hospitalizations was stratified into 2 groups based on HIV status to determine whether there were differences in demographic factors, complications, and mortality. All analyses accounted for the NIS sampling design. Results: There were 39, 404, 956 pregnancy-related hospitalizations identified; of which, 51, 762 were also associated with a positive HIV status. There were differences in complications for those with and without HIV, which included eclampsia (1.27% vs. 0.45%; P < 0.001), preterm labor (11.81% vs. 6.41%; P < 0.001), gestational diabetes (0.92% vs. 0.38%; P < 0.001), group B strep (0.03% vs. <0.01%; P < 0.001), and Gram-negative infection (0.07% vs. 0.03%; P = 0.013). After adjusting for mortality risk, calendar year, age, race and ethnicity, insurance, and zip-code level income, it was found that a positive HIV status was associated with a 91.1% increased odds of mortality (95% CI: 3.9%–351.5%; P = 0.037). Conclusion: As ART are readily available, we expected better outcomes for our HIV-positive pregnant females. Our results are concerning that there is such an increase rate of mortality and health disparity in HIV-positive pregnant females. As this is a retrospective study, there are limitation and further studies need to be conducted. Disclosures: All authors: No reported disclosures.